Agronomical valorization of eluates from the industrial production of microorganisms: Chemical, microbiological, and ecotoxicological assessment of a novel putative biostimulant - Bellotti, Gabriele; Taskin, Eren; Guerrieri, Maria Chiara; Beone, Gian Maria; Menta, Cristina; Remelli, Sara; Bandini, Fabrizio; Tabaglio, Vincenzo; Fiorini, Andrea; Capra, Federico; Bortolaso, Rossella; Sello, Simone; et al. (Frontiers in Plant Science, 2022)
Plant Biostimulants (BS) represent a valid supplement to be added or partially integrated with conventional fertilization practices. Research in the BS field keeps providing alternative products in support of both organic and conventional agriculture. Between the BS categories, protein hydrolysates (PHs) are often reported to be effective. For this reason, the eluate obtained as a by-product from the industrial production of microorganisms was studied for the improvement of soil characteristics and fertility. To our knowledge, microbial eluates have never been tested as BS despite their content of bioactive compounds and their aminoacidic composition is similar to other products on the market. Moreover, eluates utilization is in line with the circular economy principle, creating economical value for an industrial waste product. The research focused on the study of physical, chemical, biochemical, and microbiological changes occurring in agricultural soil treated with the biowaste eluate, applied at three different dosages. The final aim was to demonstrate if, and to what extent, the application of the eluate affected soil quality parameters and the composition of soil-borne microbial communities. Results indicate that the eluate application does not have a pronounced effect on the soil chemical parameters tested, and neither on the biochemical proprieties, only the higher dosage applied showed improvement in some enzyme activities or chemical composition. On the other hand, microbial communities were strongly influenced by the eluate, showing a reduction in the bacterial biodiversity and an increase for the fungal biodiversity. Bioinformatic analysis revealed that some Operative Taxonomic Units (OTUs) promoted by the eluate application, belong to known plant growth promoting microbes. Some other OTUs, negatively influenced were attributed to known plant pathogens, mainly Fusarium spp. Finally, the ecotoxicological parameters were also determined and allowed to establish that no toxic effect occurred upon eluate applications onto soil.